Implementation of The Stunting Prevention Policy Program In Cikawao Sub-District, Lengkong District, Bandung City - Susilawati Susilawati; Istikomah Istikomah; Susniwati Susniwati (Program Pascasarjana Universitas Negeri Makassar, 2023)
The stunting problem in Indonesia has not been effectively addressed so far, due to policy implementers' inability to effectively actualize the policy. Addressing a significant national problem requires appropriate policies to accelerate problem-solving efforts. This study aims to determine the implementation of the stunting prevention program policy in Cikawao sub-district, Lengkong district, Bandung city. The research method used in this study is descriptive research with a qualitative approach. The data collection techniques used in this study are in-depth interviews, observation, and documentation. Meanwhile, the data analysis technique uses Milles et.al (2014) which consists of data reduction, data presentation, and conclusion drawing or verification. Based on the research results and discussion, it can be concluded that the implementation of the Stunting Prevention Program Policy in Cikawao sub-district, Lengkong district, Bandung city using the G. Edward III theory has been running quite well. However, some aspects need improvement, such as communication, which includes transmission factors, clarity, and consistency between implementers and the community, the resources, which include staff, information, facilities, and authority, also need to be improved. On the other hand, the disposition or behavior of policy implementers has been quite good.